TTHE EFFECT OF LEVERAGE, FIRM SIZE, PROFITABILITY, AND OPERATING ACTIVITIES ON EARNINGS QUALITY OF CONSUMER NON-CYCLICALS LISTED ON IDX - Heskya Lintang Surya Andhini; Beby Hilda Agustin; Imarotus Suaidah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the effects of leverage, firm size, profitability, and operating activities on the earnings quality of Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX) during 2021–2025. This sector was chosen because its relatively stable demand provides a suitable context for assessing earnings quality. Secondary data from annual financial statements were analyzed using multiple linear regression on 205 firm-year observations obtained through purposive sampling. The findings indicate that leverage has no significant effect on earnings quality. In contrast, firm size has a significant positive effect, whereas profitability and operating activities have significant negative effects. Collectively, the independent variables significantly explain earnings quality, with an adjusted coefficient of determination of 20.7%. These results broaden empirical evidence on earnings quality within the Consumer Non-Cyclicals sector and provide useful considerations for investors, corporate managers, and other stakeholders when evaluating the credibility of reported earnings.